E-COMIC GEN ABCD: PENGEMBANGAN SUPLEMEN AJAR IPS MATERI INTERAKSI SOSIAL KELAS VII SMP: E-COMIC GEN ABCD: PENGEMBANGAN SUPLEMEN AJAR IPS MATERI INTERAKSI SOSIAL KELAS VII SMP - Ilma Naila Afina; Khofifatu Rohmah Adi; Agung Wiradimadja (Jurnal Penelitian dan Pendidikan IPS, 2022)
The limited application of face-to-face learning has obstacles and challenges. As happened at MTs Al-Manar Prambon, there is a potential for decreased motivation to explore material and learning outcomes in social studies subjects. This requires teachers to innovate in learning activities. The aims of this research are 1) designing, 2) producing, 3) testing the feasibility of the product and 4) the practicality of e-comic. This study uses the ADDIE model R&D method which consists of 5 stages: analysis, design, development, implementation and evaluation. The types of data obtained are quantitative data and qualitative data. The validation process is carried out by material expert validators and media experts, as well as practicality by education practitioners and students. The results of the feasibility test that have been carried out have obtained a percentage of 93.1% for material validation and 91.6% for media validation. Based on the percentage of expert validation, it was declared "very feasible" to be used. The practicality test was carried out on the test subject with the acquisition of a percentage of 92.8% for the results of the teacher's response and 90,1% for the results of the student's response. Based on the percentage of user responses, it is stated that it is "very practical" to be used in social studies learning material for social interaction.